Gold nanoparticles synthesized using Panax ginseng leaves suppress inflammatory - mediators production via blockade of NF-κB activation in macrophages. (17th February 2017) - Ahn, Sungeun; Singh, Priyanka; Castro-Aceituno, Verónica; Yesmin Simu, Shakina; Kim, Yu-Jin; Mathiyalagan, Ramya; Yang, Deok-Chun
Abstract: In the present study, we report that Gold nanoparticles (AuNPs) synthesized using the leaf extract of Panax ginseng Meyer ( P.g AuNPs) exert anti-inflammatory effects through inhibition of downstream NF-κB activation in macrophages. We found that P.g AuNPs reduced the expression of the inflammatory mediators including nitric oxide (NO), prostaglandin E2 (PEG2 ), interleukin (IL)-6, tumor necrosis factor-α (TNF-α) was attenuated by P.g AuNPs. Furthermore, P.g AuNPs suppressed lipopolysaccharide (LPS)-induced activation of NF-κB signaling pathway via p38 mitogen-activated protein kinase (MAPK) in RAW 264.7 cells. Taken together, our results suggest that P.g AuNPs can be utilized as a novel therapeutic agent for the prevention and cure of inflammation.